Permafrost distribution in the southern part of the discontinuous zone in Quebec and Labrador - Brown, R. J. E. (1979)
The distribution of permafrost in the southern part of the discontinuous zone in Quebec and Labrador is described. At the southern limit of this subzone islands of permafrost vary in extent from a few tens of square metres to several hectares and in thickness from a few centimetres to a metre or so. Northward to the middle of the discontinuous zone permafrost becomes increasingly widespread reaching a thickness exceeding 100 metres. Permafrost occurs mainly in peatlands, on some north facing slopes and above treeline on mountain summits. The relationships of permafrost distribution to climatic and terrain factors, including air temperature, vegetation, drainage and snow cover are discussed, the last being particularly important. The paper concludes with an analysis of some prominent air photo patterns. La répartition du pergélisol dans la partie méridionale de la zone discontinue du Québec-Labrador est décrit. Au sud de la zone de pergélisol discontinu, la superficie des îlots de pergélisol varie entre quelques dizaines de mètres carrés et plusieurs hectares et l'épaisseur du pergélisol se situe entre quelques centimètres et environ un mètre. En se dirigeant vers le nord, jusqu'au centre de la zone discontinue, le pergélisol devient plus dense et son épaisseur dépasse la centaine de mètres. Le pergélisol se manifeste surtout dans les tourbières, sur les versants exposés au nord et sur les sommets au-dessus de la limite arboréenne. Il est ensuite question des relations entre la répartition du pergélisol et les caractéristiques du climat et du terrain telles la température de l'air, la végétation, les conditions de drainage et l'épaisseur de la neige, ce dernier aspect étant particulièrement important. L'étude se termine par une analyse des traits saillants de quelques photos aériennes. Peer reviewed: Yes NRC publication: Yes